NEW APPROACHES IN MONETARY POLICY MATTERS OF THE NATIONAL BANK OF ROMANIA (NBR) FOLLOWING THE OUTBREAK OF THE INTERNATIONAL FINANCIAL CRISIS - SBÂRCEA IOANA RALUCA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2012)
The monetary issue is a current one, given the fact that now, through this component of the economicpolicy, the monetary authority of each state tries to solve the problems considered essential for each economyseparately. Through this article I will try to capture the main changes that have been made regarding theimplementation of the monetary policy of the NBR following the international financial crisis. The fact is that theNational Bank of Romania’s approach has changed, in the sense that the objective of targeting the inflation hasbecome a secondary one and the actions for supporting the economy and the Romanian banking system have takenthe first place. Thus, we showed that approaches of the National Bank of Romania before and after the financialcrisis. Thus, we observed the opposite sense in using the main monetary policy instruments, namely encouragingliquidity absorption from the market before 2008, through practicing high levels of the reference rate and of theminimum mandatory reserves and through encouraging the liquidity provision in the market after 2008 by graduallyreducing the benchmark interest rate and the mandatory reserve ratio. At first sight the purpose of this newapproach is obvious, namely credit growth for an economic recovery. This is possible under the conditions thatthese loans are addressed to the corporations directly productive that can contribute to achieving this goal. InRomania, however, these measures had as a result a significant increase of the loans granted to the state, an aspectthat contributes to indebtedness of the economy and not to its recovery.